Knowing the right person in the right place: Political connections and economic growth - Giorgio Bellettini; Carlotta Berti Ceroni; Giovanni Prarolo (Fondazione Eni Enrico Mattei (FEEM), 2009)
We develop a model of Schumpeterian growth where political connections with long-term politicians can be exploited by low-quality producers to defend their monopoly position and prevent innovation and entry of high-quality competitors. Through personal relationships developed with the incumbent politicians, connected firms are able to reduce bureaucratic costs that are set by the politicians in order to affect their chances of re-election. We focus on the stationary Markov perfect equilibria that are generated by the strategic interaction between politicians, firms and voters and show the dependence of the equilibrium on technological and political parameters. Under certain configurations, a political equilibrium arises where the politician secures re-election by setting high bureaucratic costs and firms invest in network blocking innovation and entry. Though inefficient, this equilibrium is supported by voters who prefer the status quo. Thus, the model provides a possible explanation for the persistence of inefficient democracies where these reflect shared rather than conflicting interests.
Keywords: O43; 330; Political Connections; Growth; Innovation